Decadal changes (1980’s to 2000’s) of upper ocean carbon fluxes in the Mediterranean Sea - Antoine, David; Taillandier, V.; D'Ortenzio, F. (AGU, 2010)
The air-sea CO2 flux, the carbon export to the deep layers, and more generally the carbon budgets are presently poorly characterized in the Mediterranean Sea. A first estimation of these fluxes at the scale of the Mediterranean Sea was proposed by D’Ortenzio et al. (2008). They used an approach based on an array of unconnected 1D physical-biological-chemical coupled models and assimilation of satellite information (in particular SeaWiFS ocean color observations). The simulations included the upperocean physical and biogeochemical dynamics of the entire Mediterranean Sea over the years 1998 to 2004. Here, the same approach is used to evaluate decadal changes of carbon fluxes over the entire Mediterranean Sea from the 1979-1983 to the 1998-2001 time periods, which correspond to the era of the CZCS and SeaWiFS satellite ocean color sensors. The rationale here is to use a coherent forcing over this ~20 year time period, made of satellite observations of ocean color and sea-surface temperature, of wind and heat fluxes from atmospheric models re-analyses. The simulations show that the Mediterranean Sea evolved from being a slight source of CO2 for the atmosphere during the 1980’s to a slight sink in the 2000’s. A significant increase of carbon export toward the deep layers is also revealed. Changes in fluxes are discussed, as well as changes of the respective roles of the physical and biological processes in shaping the pCO2 seasonal evolution.